2015
DOI: 10.1097/ppo.0000000000000115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Human Papillomavirus in Oropharyngeal Cancer

Abstract: Purpose The global incidence of oropharyngeal squamous cell carcinoma (OPSCC) has been increasing, and it has been proposed that a rising rate of human papillomavirus (HPV) associated cancers is driving the observed changes in OPSCC incidence. We carried out this systematic review to further examine the prevalence of HPV in OPSCC over time worldwide. Methods A systematic literature search was performed to identify all articles through January 31, 2014 that reported on the prevalence of HPV in OPSCC. Articles… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
160
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(167 citation statements)
references
References 48 publications
4
160
0
3
Order By: Relevance
“…This contrasts with previous data, detailing an increased proportion of HPVpositive OPSCC associated with increasing incidence of OPSCC overall. [8] Recent data from North America [10] and Stockholm, [23] however, suggest that plateaus in the proportion of HPV-positive OPSCC and HPV-positive tonsillar squamous cell carcinoma respectively, have been observed from the year 2000 onwards.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This contrasts with previous data, detailing an increased proportion of HPVpositive OPSCC associated with increasing incidence of OPSCC overall. [8] Recent data from North America [10] and Stockholm, [23] however, suggest that plateaus in the proportion of HPV-positive OPSCC and HPV-positive tonsillar squamous cell carcinoma respectively, have been observed from the year 2000 onwards.…”
Section: Discussionmentioning
confidence: 99%
“…Substantial variation has been reported in the proportion of OPSCC attributable to HPV between countries and time periods. [10,11] This is likely to be a reflection of variations in multiple factors, including sexual behaviour and rates of genital HPV infection, as well as tobacco and alcohol consumption. This highlights that trends in the aetiology of OPSCC must be considered in a population-specific manner.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, a study in London, Ontario, was restricted to patients with tonsillar cancer for whom a pathology specimen was available; 17 one study in Toronto included only 22 patients with oropharyngeal cancer; 18 other Toronto-based studies either took place before routine HPV testing 12 or focused on recurrent or metastatic disease; 19 and one study in Montréal analyzed patients with locally advanced cancer who were treated with primary chemoradiation and had a minimum 3-year follow-up. 20 A previous study of 1374 Ontario-based patients with oropharyngeal cancer suggested that 66% of cases were HPV-positive by 2010.…”
Section: Discussionmentioning
confidence: 99%
“…However, there have been contradictory reports showing either no or poor associations with outcome. Nevertheless, the growing proportion of HPV-positive cases poses an urgent need for prognostic biomarkers that guide patient management according to HPV status 3,6,8,9 .…”
Section: Introductionmentioning
confidence: 99%